Collaborative Governance dalam Program Pekarangan Pangan Bergizi (P2B) untuk Mendukung Ketahanan Pangan di Kabupaten Sidoarjo - Arnita Putri Wulandari; Putri Septriana Haganta Ginting; Moniqe Kurnia Hidayati Zulkarnain; Tukiman (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze how the implementation of collaborative governance in the Nutritious Food Yard Program (P2B) strengthens community-based food security in Sidoarjo Regency. A qualitative approach with a case study method was used to explore the social dynamics in depth. The research was conducted in Kampung Edukasi Sampah, Sekardangan Sub-district, one of the active areas in P2B implementation. Data were collected through interviews, observations, and document analysis involving key stakeholders such as the Sidoarjo City Food and Agriculture Office, Sidoarjo Police Sector, village officials, farmer groups, and environmental cadres. The analysis applied the collaborative governance model by Ansell and Gash (2008), which includes five indicators: face-to-face dialogue, trust building, commitment to the process, shared understanding, and intermediate outcomes. The findings show that most indicators of collaboration have been realized, particularly in communication and trust-building aspects. However, some challenges remain, including the absence of formal agreement documents among actors, inconsistent communication, lack of program outreach, and overlapping roles between the police and related agencies. This research contributes to strengthening cross-sectoral collaboration models in community-based food security programs in urban areas.